Analyzing the Role of Magnetic Features in Additive Manufactured Scaffolds for Enhanced Bone Tissue Regeneration. Issue 1 (16th April 2021) - De Santis, Roberto; Papallo, Ida; Onofrio, Ilaria; Peluso, Valentina; Gallicchio, Vito; Rega, Andrea; D'Antò, Vincenzo; Improta, Giovanni; Catauro, Michelina; Gloria, Antonio; Russo, Teresa
Abstract: The concept of magnetic guidance has opened a wide range of perspectives in the field of tissue regeneration. Accordingly, the aim of the current research is to design magnetic responsive scaffolds for enhanced bone tissue regeneration. Specifically, magnetic nanocomposite scaffolds are additively manufactured using 3D fibre deposition technique. The mechanical and magnetic properties of the fabricated scaffolds are first assessed. The role of magnetic features on the biological performances is properly analyzed.